Holistic patterns as an instrument for predicting the performance of promising young soccer players - A 3-years longitudinal study - Zuber, C.; Zibung, M.; Conzelmann, A. (Frontiers in Psychology, 2016)
Multidimensional and dynamic talent models represent the current state of the art, but these demands have hardly ever been implemented so far. One reason for this could be the methodological problems associated with these requirements. This paper will present a proposal for dealing with this, namely for examining the development of young soccer players holistically. The patterns formed by the constructs net hope, motor abilities, technical skills and biological maturity were examined, as well as the way in which these holistic patterns are related to subsequent sporting success. 119 young elite soccer players were questioned and tested three times at intervals of 1 year, beginning at the age of 12. At the age of 15, the level of performance reached by the players was determined. At all three measuring points, four patterns were identified, which displayed partial structural and high individual stability. The highly skilled players, scoring above average on all factors - but not necessarily those having the highest overall scores - were significantly more likely to advance to the highest level of performance. Failure-fearing fit players, i.e., physically strong, early developed players but with some technical weaknesses, have good chances of reaching the middle performance level. In contrast, none of the achievement-oriented, highly skilled, late-matured or late-matured, low skilled players reached the highest performance level. The results indicate the importance of holistic approaches for predicting performance among promising soccer talents in the medium-term and thus provide valuable clues for their selection and promotion.